The Effect of Promotion on Interest in Opening an Account at Bank Muamalat, Palu Branch - Gita Dolita; Hilal Malarangan; Malkan Malkan (AL-ARBAH: Journal of Islamic Finance and Banking, 2021)
Purpose - The purpose of this study was to determine whether promotion has an effect on the interest of Islamic banking students in opening an account at the hammer branch of the muamalat bank and to find out how significant the effect of promotion is on student interest in opening an account at the hammer branch of the muamalat bank.Method - This study uses primary data, namely a questionnaire that uses a Likert scale as a calculation scale. The sample of this study was 485 students of the Faculty of Economics and Islamic Business IAIN Palu, Department of Islamic Banking from class 2016 to class 2018. To analyze the data, the authors used multiple linear regression methods and SPSS version 21. Result - Research result shows that the magnitude of the influence of the variable (X) on the variable (Y) is 0.388 or 38.8%. These results can provide an illustration that respondents (students) view that promotion can influence student interest in opening an account at a muamalat bank and promotion has a significant effect on student interest in opening an account at a muamalat bank. it can be seen that the promotion variable (X) has a value of tcount 3.783> t table 1.663 and has a significant value (sig) of 0.000 in the coefficients table with a value of α (significant level) 0.05. This means 0.000 <0.05.Implications - This study is only limited to using data from several students in one university. Originality-. The difference with previous research is in the location and object under study.